(untitled) (Journal of Medical & Health Sciences Review, 2025)
Severe orofacial and deep-neck space infections (DNSIs) represent a medical emergency during pregnancy due to their potential to rapidly compromise maternal and fetal health. These infections commonly arise from odontogenic sources and can progress into the cervical fascia, mediastinum, or airway, particularly in immune-altered states like pregnancy. The maternal physiological adaptations of gestation—including reduced cell-mediated immunity, increased plasma volume, and mucosal edema—amplify the severity and complicate the management of such infections. This systematic review aimed to investigate the multidisciplinary approaches used in managing severe orofacial and DNSIs in pregnant patients worldwide, analyze outcomes, and provide clinical insight into best practices. We performed a systematic search across PubMed, Scopus, and Embase from January 2000 to May 2025. We included case reports, case series, and observational studies that specifically documented DNSI or orofacial infections in pregnant patients managed through multidisciplinary care. A total of 52 studies comprising 88 patients were included in the final analysis. The findings emphasized the necessity of early diagnosis, aggressive antibiotic therapy, surgical drainage, and airway management. Multidisciplinary teams—often including oral and maxillofacial surgeons, obstetricians, otolaryngologists, anesthesiologists, and infectious disease specialists—were critical in most cases. Imaging was often limited to MRI and ultrasound due to fetal safety concerns, while antibiotic selection favored penicillin, cephalosporins, and metronidazole. Surgical intervention was necessary in 83% of cases, with 31% requiring ICU admission and 27% undergoing airway protection via tracheostomy or intubation. Maternal outcomes were favorable in 92% of cases, but fetal complications occurred in 12%, mainly preterm labor and intrauterine growth restriction. Delays in diagnosis, referral, or surgical intervention were linked to worse outcomes. This review reinforces the role of multidisciplinary care and the importance of early, standardized protocols in managing such high-risk cases. Regional disparities also highlight the need for improved access to tertiary care and interdisciplinary collaboration globally.